Solving multi objective power flow problem using enhanced sine cosine algorithm - Shaik Karimulla (Elsevier, 2021)
In the electrical power system optimal power flow is a solution for power management with multi variable equality and inequality constraints. Different algorithms were used to solve the optimum power flow (OPF). This paper proposes the optimal power flow using efficient and reliable optimization technique of enhanced sine cosine algorithm (ESCA). The proposed algorithm used to solve the multi objective power flow function problems such as generating cost, losses, emission of power plant and to improve the voltage stability. In this IEEE standard 30 bus system with four different multi objective functions have been tested and results obtained by Enhanced sine cosine algorithm are compared with other evolutionary algorithms. The results show that ESCA gives better results than other techniques in terms of convergence speed and global optimal solutions.